Motor learning and performance from principles to application - Schmidt, Richard A. 1941-2015 (Richard Allen); Lee, Timothy Donald 1955- (Human Kinetics, 2020)
Motor learning and performance: from principles to application, sixth edition, enables students to appreciate high-level skilled activity and understand how such incredible performance occur. Written in a style that is accessible even to students with little or no knowledge of physiology, psychology, statistical methods, or other basic sciences, this text constructs a conceptual model of factors that influence motor performance, outlines how motor skills are acquired and retained with practice, and shows how to apply the concepts to variety of real-world settings. The sixth edition has been carefully revised to incorporate the most important research findings in the field, and it is supplemented with practice situations to facilitate a stronger link between research-based principles and practical applications